Opposition Visions for Preserving Syria's Ethnic-Sectarian Mosaic - Rustum Mahmoud; Stephan Rosiny (German Institute of Global and Area Studies (GIGA), 2015)
The excessive violence that has spread across virtually all of Syria since the 2011 uprising against the regime of Bashar al-Assad has so far prevented a serious debate about feasible solutions. Most political factions fear that any talk of a compromise solution will undermine their own position among their followers and benefit the other side by granting it recognition. The opposition refuses to negotiate with a dictator who has too much blood on his hands, while the regime declines to negotiate with "terrorists." Fear of exclusion in a future order dominated by radical Islamist forces is keeping the minority groups and some secularists close to the regime. This vicious circle of repudiation and fear has strengthened threat perceptions and has caused a military stalemate. However, there are also grounds for cautious optimism: as this paper shows, most actors from the moderate opposition acknowledge the need to take the minorities' fears seriously and to provide them with guarantees of participation in a future political order, while stopping short of the option of a power-sharing arrangement between community representatives.
Keywords: 300; power-sharing; civil war; opposition; sectarianism; Syria